The relationship between perceived leadership and local fishers' level of participation in coastal management activities in Nasidman Island, Ajuy, Iloilo - Cordero, Cleto H.
This study described the relationship between perceived leadership capabilities and local fishers' level of participation in the phases (planning/decision making, implementation and monitoring) of coastal management activities. This als determined the lcoal fishers' level of perception towards leadership and level of participation and coastal management activities. Conducted in Nasidman, Ajuy, this study used forty local fishers as respondents, all of which are members of NASFA. Their responses were gathered with the use of Likert measurement scale and verbal frequency scale., The results of this study on perception and participation were analyzed using descriptive statistics while Pearson Correlation Coefficient at .05 level was used to determined the relationships of the variables. The findings showed that local fishers have significantly high level of perception towards leadership capabilities and also relatively high level of participation in coastal management activities. Statistical computation using Pearson Correlation showed that there is a significant relationship between perceived leadership and local fishers' level of participation in the planning/decision making implementation and monitoring of hook and line and artificial reef projects since the computed value is greater than r-critical. The researchers recommend that the local government should create a program to develop and assist the leaders of the coastal community to continuously lead the local fishers in the planning, implementation and monitoring of coastal management activities. Moreover, the local government should create programs to mold the personality and leadership styles of the leaders since these would elicit active participation among the local fishers in the activities of the community.